Rancang Bangun Sistem Informasi Klinik Praktik Dokter Berbasis Web - IP Agus Yoga Permana (LPPM Universitas Dhyana Pura, 2015)
Physician services practice together is a practice that there is more than one general practitioners and specialists who work in public health services. For that we need a system that can improve the effectiveness and efficiency of work. In addition, many clinics still use manual way to record all patient health data, making the data difficult to control the patient's health and the result of human error can not provide accurate information. So far, in terms of patient health record data, thus affecting the efficiency and effectiveness of the work, so that service to patients becomes very slow. In this thesis, the author tries to apply the concept of clinical information systems web- based physician practices to manage patient data, physician data, drug data, the data measures and medical record data with the help of a computer, since the patients come for treatment, medical history records (medical records ) patients, until the drug supply data, for decision-making and maintenance of the database. Information systems are designed using PHP and MySQL as the database could be a solution to the problems faced.Keywords: Information Systems, Clinical, Web